ANALISIS SURVIVAL WAKTU DISKRIT - , DJATI SAMPURNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The continuous-time proportional hazard model based on the assumption which is not realistic that the predictor effect when the event occur is constant all the time. There are some cases that the value of predictor can be varies from time to time. Because of that, the discrete-time survival analysis is used as common approach survival analysis to solve this problem. The predictor which value is varies from time to time can be modeled such as time-invariant. Singer and Willet (1993) showed that the model can be fit to use the logistic regression analysis and to use the likelihood maximum procedure to estimate itâs parameter. By use the AIDS data patient with STRATUM and CD4 predictors, will be explained the different between both of predictors in interpretation.